The Colony of New Jersey - Whitehurst, Susan (New York The Rosen Publishing Group,Inc, 2000)
Relates the history of the colony of New Jersey from its founding in 1664 to statehood in 1787.
Keywords: New Jersey -- History -- Colonial period, ca. 1600 - 1775.; Series: The library of the thirteen colonies and the lost colony; New Jersey -- History -- 1775 - 1865.